Sixth Grade Students’ Difficulties in Learning English At Muhammadiyah 1 Elementary School - Mulki Yustinto; Solehan (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
Learning English at the elementary level often presents various challenges for students, particularly in contexts where English is taught as a foreign language. This study aims to investigate the difficulties faced by sixth grade students in learning English at Muhammadiyah 1 Elementary School. The research employed a descriptive qualitative design. The subjects of the study were sixth grade students, selected through purposive sampling. Data were collected using classroom observations, questionnaires, and interviews to gain comprehensive insights into students’ learning difficulties. The findings reveal that students experience several major difficulties, including limited vocabulary mastery, problems with pronunciation, low understanding of grammar, and lack of confidence in speaking English. In addition, insufficient exposure to English outside the classroom and limited learning media were found to contribute to these difficulties. These challenges negatively affect students’ motivation and participation during English lessons. The study implies that teachers need to apply more interactive teaching strategies, provide varied learning media, and create a supportive learning environment to reduce students’ difficulties in learning English. Improving teaching methods is expected to enhance students’ English learning outcomes at the elementary level.